2007
DOI: 10.1145/1268517.1268552
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the design space of referencing in collaborative augmented reality environments

Abstract: For collaborative environments to be successful, it is critical that participants have the ability to generate effective references. Given the heterogeneity of the objects and the myriad of possible scenarios for collaborative augmented reality environments, generating meaningful references within them can be difficult. Participants in co-located physical spaces benefit from non-verbal communication, such as eye gaze, pointing and body movement; however, when geographically separated, this form of communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 24 publications
(16 reference statements)
0
23
0
Order By: Relevance
“…In computer-mediated collaboration multiple people may even share exactly the same viewpoint. In the context of remote collaboration this approach has been shown to be beneficial as occlusion issues are prevented and referential ambiguity can be minimized (Chastine et al, 2007;Kraut et al, 1996).…”
Section: Referential Awarenessmentioning
confidence: 99%
See 2 more Smart Citations
“…In computer-mediated collaboration multiple people may even share exactly the same viewpoint. In the context of remote collaboration this approach has been shown to be beneficial as occlusion issues are prevented and referential ambiguity can be minimized (Chastine et al, 2007;Kraut et al, 1996).…”
Section: Referential Awarenessmentioning
confidence: 99%
“…In fact, earlier research on remote assistance systems suggests the contrary. Chastine et al (2007) reported that users appreciate the advantages of sharing virtually the same viewpoint even if this involves their view being partially occluded by a semi-transparent avatar representation. Obviously, an avatar does not provide the same level of copresence as a real person.…”
Section: Proxemicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A different technique that resembles the approach taken in our studies is to share only virtual aspects while maintaining independent physical halfworlds for each participant, resulting in a rather virtual experience with directness of augmented reality interaction. Among others, Chastine et al [9] used this approach in their studies and highlight the problem of referencing in AR collaboration.…”
Section: Related Workmentioning
confidence: 99%
“…Based on a pedagogically driven reference scenario of a learning unit, we have implemented a simple prototypical AR application for using AR in schools and evaluated it in a field test under classroom-similar conditions. While summative evaluations [3] found a high acceptance rate among students and teachers and confirmed the pedagogical effectiveness of the prototype AR application, the formative evaluation resulted in a number of recommendations informing future development: sharing viewpoints could simplify referencing problems in communication (see also [9]), video-conferencing features could avoid uncertainties related to remote presence and traditional HumanComputer Interaction features such as Undo could improve ease of use. Overall however, the formative evaluation found that the prototype is well suited for hands-on remote collaboration, and that minor implementation issues are more than compensated for by students' resilience and motivation to complete their collaborative tasks in the shared AR space.…”
Section: Conclusion and Further Workmentioning
confidence: 99%